Stregoneria e utopia. Luciano Parinetto vent’anni dopo (Materiali di Estetica. Terza serie, 2022)
Twenty years after his death, the reflections of Luciano Parinetto (1934-2001), who was associate professor of Moral Philosophy at the University of Milan, remain, on the one hand, on the relationship between witchcraft and diversity, and on the other hand, on the value of utopian hope. Despite the fact that the course of history has preferred the path of integration to that of revolution, dialectics remains the picklock to criticize alienated social situations.
Keywords: Revolutionary Dialectic; Utopian Hope; Diversity; Witchcraft